Looking beyond comparative descriptions of subject behaviours: a pedagogically motivated qualitative study of research results in applied linguistics and education - Lim, Jason,Miin Hwa (2011)
Guiding novice research paper writers to present findings may form an essential component in an ESP course at the tertiary level. To enlighten second language learners on the possible types of findings generally presented in the Results section of research papers, the researcher analysed seven categories of results in journal articles on applied linguistics and education. By means of a genre-based approach recommended by Swales (1990; 2004) and employed by Brett (1994), various categories of findings were analysed with reference to both rhetorical functions and prominent linguistic resources. The results have shown that text segments related to findings may exhibit distinctly different linguistic characteristics that need to be highlighted in exercises aimed at helping learners distinguish categories of findings. This investigation is of considerable pedagogical significance, in that the close link between experienced writers’ communicative intentions and their linguistic choices can be effectively demonstrated to help learners present findings in the two academic fields.